TSE past, present, and future - Miles, John (Philippine Journal of Linguistics, 2003)
This paper will summarize the development and status of the Test of Spoken English (TSE), discuss its strengths as an assessment of speaking proficiency, and indicate ways in which TSE will change to meet new demographic and technological needs as well as conceptual demands. Originally, the TSE was intended to test international students desiring to become teaching assistants at North American universities. Because of U.S. immigration agency rulings in 1997 and decisions by various professional licensing boards, the test is taken by increasingly large numbers of medical and educational professionals. Revised in 1995 to be more communicative, the current TSE is a booklet-and tape-mediated test of general English speaking ability formulated to elicit a series of monologic speech samples. These recorded samples are evaluated at ETS by trained, certified and calibrated raters, who score each item holistically against the TSE Rating Scale. The test is statistically extremely reliable, with both high inter-rater reliability and high internal consistency between items. Given changes in candidate demographics, in technology, and in linguistic concepts about speech, however, as well as the introduction of a speaking component in the new TOEFL test beginning July 2004, TSE will also change. Rather than a radical transformation that could be disturbing to test-takers, raters, and users (universities and licensing boards), a gradual evolution of the test is envisaged. Beginning in January 2003, for example, new item types will be pre-tested at successive administrations, and become operational by mid-year. Technological developments in the administration of TSE, such as digitization of test and sound files, are also expected.